Engineering of electrochromic materials as activatable probes for molecular imaging and photodynamic therapy - Wu, Luyan (2020)
Electrochromic materials (EMs) are widely used color-switchable materials, but their applications as stimuli-responsive biomaterials to monitor and control biological processes remain unexplored. This study reports the engineering of an organic π-electron structure-based EM (dicationic 1,1,4,4-tetraarylbutadiene, 12+) as a unique hydrogen sulfide (H2S)-responsive chromophore amenable to build H2S-activatable fluorescent probes (12+-semiconducting polymer nanoparticles, 12+-SNPs) for in vivo H2S detection. We demonstrate that EM 12+, with a strong absorption (500–850 nm), efficiently quenches the fluorescence (580, 700, or 830 nm) of different fluorophores within 12+-SNPs, while the selective conversion into colorless diene 2 via H2S-mediated two-electron reduction significantly recovers fluorescence, allowing for non-invasive imaging of hepatic and tumor H2S in mice in real time. Strikingly, EM 12+ is further applied to design a near-infrared photosensitizer with tumor-targeting and H2S-activatable ability for effective photodynamic therapy (PDT) of H2S-related tumors in mice. This study demonstrates promise for applying EMs to build activatable probes for molecular imaging of H2S and selective PDT of tumors, which may lead to the development of new EMs capable of detecting and regulating essential biological processes in vivo.